Підвищення стійкості криптоалгоритму RSA за рахунок генетичної оптимізації вихідного повідомлення - Приймак, А.В.; Яремчук, Ю.Є. (Реєстрація, зберігання і обробка даних, 2018)
Розглянуто існуючі асиметричні алгоритми шифрування інформації. Описано їхні переваги та недоліки. Проведено дослідження алгоритму RSA щодо можливості підвищення його криптостійкості. Запропоновано метод оптимізації вихідного повідомлення за допомогою генетичного алгоритму. Представлено статистичне тестування запропонованого покращення алгоритму, яке показало, що отримані показники статистичної безпеки є вищими за показники оригінального алгоритму на 1–3 %. Рассмотрены существующие асимметричные алгоритмы шифрования информации. Описаны их преимущества и недостатки. Проведено исследование алгоритма К.8А о возможности повышения его криптостойкости. Предложен метод оптимизации исходного сообщения с помощью генетического алгоритма. Представлено статистическое тестирование предложенного улучшения алгоритма, которое показало, что полученные показатели статистической безопасности являются выше показателей оригинального алгоритма на 1-3 %. The research of the cryptographic algorithm RSA with regard to the possibility of increasing its stability by using genetic algorithm was made. The method of optimization of input message consisting of 8 main steps, with the help of genetic algorithm is proposed. Using the three main properties of the genetic algorithm (selection, crossover and mutation), the input message is randomizing, which as a result of RSA encryption is transformed into a stochastic ciphertext, which is no longer deterministic and weak to attack based on selected ciphertext, and thus increases the cryptostability of this algorithm. The statistical testing of the proposed improvement of the algorithm, using the NIST STS test package, showed a high statistical reliability of this method, as the results of tests were inside 0,9–1 range. Comparison of the results of testing of the original RSA and the modified showed that the original algorithm shows worse performance compared to the proposed its modification. Ten of the fifteen tests showed that the modified RSA algorithm with the built-in proposed method for optimizing the input message has higher rates by 1–3 %, which shows an increase of its cryptostability.